An Online Departmental Fee Management System - Bethran Chibuike, Amanze; Bethel Chinenye, Nwoke; Leticia E, Eleberi (International Journal of Computer Sciences and Engineering, 2020)
In Universities Nationwide, there are a large number of students who pay all their fees through cash deposits, electronic cash transfer or bank drafts to the University’s account in specific bank branches. These methods have proven inefficient in more ways than one. It was upon such background that the researchers embarked on a paper aimed at developing an alternate system that enables students as well as sponsors to securely pay fees using valid credit and debit cards. Object Oriented Analysis and Design Methodology (OOADM) was employed in the design of the new system. The system was developed using hypertext preprocessor (PHP), hypertext markup language (HTML) and MySQL database. The new system assist students in paying their fees and issues them a receipt automatically.